Anniversaries of Innovative Drilling Technologies. Reference Review - Kozhevnikov А.А.; Sudakov А.К. (Science and Innovation, 2024)
The design and creation of diamond rock cutting tools, namely the big diamond drill bit; the small diamond drill bit; the bit equipped with synthetic diamonds; and the bit reinforced with composite materials using diamonds have been considered. The benchmarks of innovative development of drilling technologies have been presented.